PRODUCT Product and Service Development Strategies on Murabahah Contracts to Improve The Existence of BMT Hasanah - Mukaromah, Ni`matul Fitria; Rofiah, Khusniati; Futaqi, Faruq Ahmad (Etihad: Journal of Islamic Banking and Finance, 2024)
Introduction: Many financial institutions have developed in Ponorogo, conventional and sharia. BMT Hasanah is present as a Sharia microfinance institution that often helps households and UMKM. Even though there is much competition, BMT Hasanah can continue to show its existence. This research aims to determine product and service development strategies, especially in murabahah contracts. Research Methods: This research aims to determine product and service development strategies, especially in murabahah contracts. The research uses a qualitative approach using primary data in the form of interviews and observations and secondary data obtained from archival documents and the internet. Results: The results of this research show that BMT Hasanah is responsive in responding to customer product requests. The murabahah products provided are always up to date with straightforward guarantees. Apart from that, BMT Hasanah provides maximum service in terms of installment payments. Customers are visited using a pick-up system and also serve an installment system by transfer. Conclusion: With this strategy, BMT Hasanah not only increases competitiveness and revenue but also increases customer satisfaction, which ultimately strengthens its existence.